Offshore distribution of Hector's dolphins at Banks Peninsula, New Zealand: Is the Banks Peninsula Marine Mammal sanctuary large enough? - Elisabeth Slooten; William Rayment; Steve Dawson (New Zealand Journal of Marine and Freshwater Research, 2006)
Aerial surveys of Hector's dolphins were carried out to evaluate the effectiveness of the Banks Peninsula Marine Mammal Sanctuary. In summer, the proportion of sightings inside the 4 nautical mile offshore boundary of the sanctuary was 79%. This dropped to just over 35% in winter. These estimates were used in a population viability analysis to determine whether the sanctuary needs to be extended to reduce dolphin bycatch to sustainable levels. We followed the standard procedure for setting limits on marine mammal bycatch in the United States to calculate a bycatch limit of 1.6 or 2.8 dolphins per year (depending on whether the sanctuary population is included). If the offshore boundary was extended to 15 nautical miles, the sanctuary would need to be extended alongshore north and south by more than 30 nautical miles to reduce bycatch to 2.8, or north and south by 60 nautical miles to reduce bycatch to 1.6 dolphins per year.